Evaluasi Kesiapan Guru terhadap Implementasi Kurikulum Merdeka di Madrasah Aliyah Negeri 01 Kepahiang - Kurniawan, M Efrry; Effendi, Mardian; Kusen (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
The aim of this research is to explain teachers' readiness for implementing an independent curriculum. The type of research carried out was descriptive qualitative. The data sources used are interviews, observation and documentation. Data analysis is carried out through data reduction, data presentation, and drawing conclusions/verification. This research aims to carry out an evaluation of teacher readiness in implementing the independent curriculum, which is an important process to ensure the effectiveness and success of implementing this new curriculum. An independent curriculum is an educational approach that aims to give teachers freedom to design and implement learning according to needs and context. The results of this research are that teacher readiness does not only include conceptual understanding, but also involves the ability to carry out comprehensive assessments, commitment to professional development, and expertise in preparing Learning Implementation Plans (RPP) that are in accordance with the Merdeka Belajar Curriculum format. Carrying out an evaluation of teacher readiness can help identify the necessary development needs and provide support for teachers in overcoming the challenges that arise when implementing this curriculum. With optimal readiness, it is hoped that the implementation of the Independent Learning Curriculum can provide maximum benefits for students.